Lipiodol Lymphangiography and Glue Embolization for Vulvar and Vaginal Lymphorrhea - Meshari Alali; Rohee Park; Ji H. Shin; Chengshi Chen; Jeoung I. Shin (The Arab Journal of Interventional Radiology, 2022)
A 26-year-old woman patient had an 18-year long history of vulvar and vaginal lymphorrhea and multiple millet-like lesions on her vulva. On magnetic resonance image, multiple T2 high signal intensities were noted at the bilateral vulvar areas and pelvic cavity. Conventional lipiodol lymphangiography showed lymphatic reflux to the vulvar areas, possibly originating from prominent tubular lymphatics in the right lower abdominal wall. After percutaneous puncture of this tubular lymphatic structure, its distal portion was embolized using microcoils to prevent upward glue propagation; this was followed by glue embolization of the tubular lymphatic structure. The patient was without skin lesions or symptoms at follow-up of 1 year after the procedure.